The Influence of Tube Potential on Periodontal Bone Level Measurements and Subjective Image Quality Using a Digital Photostimulable Storage Phosphor Sensor - Reinhilde Jacobs; Bart Vandenberghe (eJournal of Oral Maxillofacial Research, 2010)
Objectives: The purpose of the present study was to determine the measurement accuracy and subjective image quality for periodontal disease diagnosis when using two X-ray tube voltages with a digital photostimulable storage phosphor sensor.Material and Methods: A digital photostimulable storage phosphor (PSP) sensor (Vistascan) and a multipulse X-ray generator (Prostyle Intra) with two tube voltages were used in this study. The front, premolar and molar region of two adult human cadaver skulls jaws were imaged using the X-ray tube at 63 kV and 70 kV, both at 8 mA and decreasing exposure times (160 ms, 120 ms and 80 ms). A standardized exposure protocol containing waxed occlusal keys and an aiming device ensured proper and reproducible beam alignment. Three observers assessed the digital radiographs for 31 selected periodontal bone loss sites. Radiographic measurements were compared to physical measurements (Standard). Subjective ratings of lamina dura, crater defect and furcation involvement visibility, contrast perception and bone quality were also performed.Results: Multiple regression equation of the variables kV and exposure time demonstrated no significant difference for the periodontal bone level measurements (P > 0.05). In 90.3% and 96.7% of the measurements for 70 kV and 63 kV respectively, deviation was within 1 mm. The subjective ratings produced similar findings in terms of image quality for both tube voltages and the three exposure times.Conclusions: The results of the present study revealed that tube voltages of 63 kV and 70 kV provided similar accuracy and image quality for periodontal disease diagnosis.